2016
DOI: 10.1002/ajmg.a.37626
|View full text |Cite
|
Sign up to set email alerts
|

Further delineation of facioaudiosymphalangism syndrome: Description of a family with a novel NOG mutation and without hearing loss

Abstract: Mutations in the NOG gene give rise to a wide range of clinical phenotypes. Noggin, the protein encoded by this gene is a secreted modulator of multiple pathways involved in both bone and joint development. Proximal symphalangism is commonly observed in patients bearing mutations in this gene, however secondary symptomes are often found including typical facies with hemicylindrical nose with bulbous tip, hyperopia, reduced mobility of multiple joints, hearing loss due to stapes fixation, and recurrent pain fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
1
8
2
Order By: Relevance
“…The affection was seen through more than four meiosis (family members of three generations), which may also confirm the pathogenicity. Substitution of Cysteine with tyrosine at position 230 has previously been reported as pathogenic [31] but in this study, we found a deletion and not a substitution. Bayat et al presented the novel mutation in NOG resulting in substitution of Cysteine 230 in a Danish family, but none of the affected family members had hearing loss [31].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The affection was seen through more than four meiosis (family members of three generations), which may also confirm the pathogenicity. Substitution of Cysteine with tyrosine at position 230 has previously been reported as pathogenic [31] but in this study, we found a deletion and not a substitution. Bayat et al presented the novel mutation in NOG resulting in substitution of Cysteine 230 in a Danish family, but none of the affected family members had hearing loss [31].…”
Section: Discussioncontrasting
confidence: 67%
“…Substitution of Cysteine with tyrosine at position 230 has previously been reported as pathogenic [31] but in this study, we found a deletion and not a substitution. Bayat et al presented the novel mutation in NOG resulting in substitution of Cysteine 230 in a Danish family, but none of the affected family members had hearing loss [31]. Another study reported a mutation in Cysteine 184 causing proximal symphalangism without hearing impairment [6].…”
Section: Discussioncontrasting
confidence: 67%
“…Therefore, it is di cult to determine the relationship between the mutations and clinical phenotype. Bayat et al proposed a new mutation in NOG in which cysteine 230 was replaced in a Danish family, but none of the affected family members suffered hearing loss [15]. Another study reported that mutations in cysteine 184 caused no indication of hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is di cult to determine the relationship between the mutations and clinical phenotype. Bayat et al proposed a new mutation in NOG in a Danish family in which cysteine 230 was replaced, but none of the affected family members suffered hearing loss [23]. Another study reported that mutations in cysteine 184 caused no indication of hearing impairment.…”
Section: Discussionmentioning
confidence: 99%